Characterization and Tensile Properties of Silane Treated Bamboo Fibre Reinforced Poly (lactic) Acid Composite - Nasyita Qabsah Mohktar, (Progress in Engineering Application and Technology, 2023)
In the couple of decades, bamboo is getting interested in producing bamboo fiber as a reinforcement agent in polymer composite due to its biodegradable characteristic and mechanical properties which can replace use of synthetic polymer. Gigantochloa Albociliata (Bamboo Madu) is the type of bamboo that has been chosen in this study. The main objectives of this study are to characterise the effect of alkali pretreatment and silane treatment on bamboo fibre, and to investigate the effect of silane treated bamboo fibre content on mechanical properties of PLA composite film. The characterisation of bamboo fibre can be accessed via Fourier Transform Infrared Spectroscopy (FTIR) analysis and Particle Size Analyzer (PSA). The pretreatment and treatment of bamboo fibre used in this study were alkali ang silane treatment respectively. Untreated and treated bamboo fibre were evaluated tensile strength using tensile test using standard ASTM D882. Finally, the outcome of this study shows that highest bamboo fibre content in PLA composite, resulting in a great tensile strength. In addition, treated bamboo fibre depicts higher tensile strength than the untreated bamboo fibre.